Nigeria : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report finds that there has been limited implementation of the 2004 Country Action Plan and limited improvement in financial reporting practices in Nigeria. Nigerian authorities have successfully implemented only 6 of 14 action plans emanating from the 2004 review leaving significant areas yet to be addressed. This 2011 ROSC presents policy recommendations that take into account international experience, good practice, and local circumstances.